Evaluasi Sistem Proteksi Kebakaran Pada Bangunan Gedung Rumah Sakit Umum Daerah Pulang Pisau: Evaluation Of The Fire Protection System In The Pulang Pisau Regional Public Hospital Building - Tarip, Tahan (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Fire is an incident that results in loss in the form of material or non-material, there are several factors that cause electrical fires, the element of intent and the lack of preparedness of the surrounding community in facing and dealing with the danger of fire and the lack of fire protection system facilities and infrastructure. Evaluation of the fire protection system refers to the Pd-T-11-2005-C regulation concerning Fire Safety Inspections of Buildings, the method used is interviews, direct observation and measurements at the location. The results of this research are the Reliability Value of Building Safety Systems for Landing Equipment Components 22.60%, Safety Suggestions 18.25%, Active Protection Systems 5.9% and Passive Protection System Components 9.36%. And the overall calculation results from the KSKB obtained a value of 56.11%